Characterization of the complete chloroplast genome of Corydalis bungeana Turcz - Qi Wang; Zhixian Lei; Lirong Zhou; Biwei Mai; Naiyun Zhu; Xiaoli Zhao; Wenting Xu (Mitochondrial DNA. Part B. Resources, 2021)
Corydalis bungeana Turcz. is a perennial herb belonging to the family Papaveraceae. Its chloroplast genome was sequenced and characterized. The cp genome of C. bungeana is 167,629 bp long with a GC content of 36.52%. A total of 144 genes were identified in this cp genome, including 79 protein-coding genes, 31 tRNAs and four rRNAs. A phylogenetic tree based on the complete nucleic acid sequence indicated that C. bungeana was classified into Corydaleae and had a close relationship with Lamprocapnos spectabilis.